Partial balance of nitrogen in a maize cropping systems in humic nitisol of Central Kenya - Kimetu, J.M.; Mugendi, DN; Bationo, B. André; Palm, Cheryl A.; Mutuo, PK; Kihara, Job Maguta; Nandwa, SM; Giller, Kenneth E. (Springer, 2007)
The application of nitrogen in a soil under agricultural production is subject to several pathways including de-nitrification, leaching and recovery by an annual crop. This is as well greatly influenced by the management practices, nitrogen source and soil conditions. The main objective of this study was to investigate the loss of nitrogen (N) through nitrous oxide (N2O) emissions and mineral N leaching and uptake by annual crop as influenced by the N source. The study was carried out at Kabete in Central Kenya. Measurements were taken during the second season after two seasons of repeated application of N as urea and Tithonia diversifolia (tithonia) leaves. Results obtained indicated that nitrous oxide (N2O) emissions at 4 weeks after planting were as high as 12.3 ?g N m ?2 h?1 for tithonia treatment and 2.9 ?g N m?2 h?1 for urea treatment. Tithonia green biomass treatment was found to emit N2O at relatively higher rate compared to urea treatment. This was only evident during the fourth week after treatment application.Soil mineral N content at the end of the season increased down the profile. This was evident in the three treatments (urea, tithonia and control) investigated in the study. Urea treatment exhibited significantly higher mineral N content down the soil profile (9% of the applied N) compared to tithonia (0.6% of the applied N). This was attributed to the washing down of the nitrate-N from the topsoil accumulating in the lower layers of the soil profile. However, there was no significant difference in N content down the soil profile between tithonia treatment and the control. It could be concluded that there was no nitrate leaching in the tithonia treatment. Nitrogen recovery by the maize crop was higher in the urea treatment (76% of the applied N) as compared to tithonia treatment (55.5% of the applied N). This was also true for the residual mineral N in the soil at the end of the season which was about 7.8% of the applied N in the urea treatment and 5.2% in the tithonia treatment.From this study, it was therefore evident that although there is relatively lower N recovery by maize supplied with tithonia green biomass compared to maize supplied with urea, more nitrogen is being lost (through leaching) from the soil plant system in the urea applied plots than in tithonia applied plots. However, a greater percentage (37.8%) of the tithonia-applied N could not be accounted for and might have been entrapped in the soil organic matter unlike urea-applied N whose greater percentage (92%) could be accounted for.